Multilingual Assessment of Early Child Development : Analyses from Repeated Observations of Children in Kenya - Knauer, Heather A. (World Bank, Washington, DC, 2019)
In many low- and middle-income countries, young children learn a mother tongue or indigenous language at home before entering the formal education system where they will need to understand and speak a country's official language(s). Thus, assessments of children before school age, conducted in a nation's official language, may not fully reflect a child's development, underscoring the importance of test translation and adaptation. To examine differences in vocabulary development by language of assessment, this study adapted and validated instruments to measure developmental outcomes, including expressive and receptive vocabulary. This study assessed 505 children ages 2 to 6 in rural communities in Western Kenya with comparable vocabulary tests in three languages: Luo (the local language or mother tongue), Swahili, and English (official languages) at two time points, five to six weeks apart, between September 2015 and October 2016. Younger children responded to the expressive vocabulary measure exclusively in Luo much more frequently than did older children: 44–59 percent of those ages 2 to 4, compared to 20–21 percent of those ages 5 to 6. Baseline receptive vocabulary scores in Luo and Swahili were strongly associated with receptive vocabulary in English at follow-up, even after controlling for English vocabulary at baseline: a multivariate regression of follow-up English vocabulary on standardized measures of receptive vocabulary in all three languages yields an estimate, for Luo, of β = 0.26, SE = 0.05, p < 0.001; and for Swahili, β = 0.10, SE = 0.05, p = 0.032. The study also found that parental Luo literacy at baseline was associated with child English vocabulary at follow-up, while parental English literacy at baseline was not: a multivariate regression on both measures, along with household controls, yielded, for Luo, β = 0.11, SE = 0.05, p = 0.045; the coefficient on English was not statistically significantly distinguishable from zero (p=0.18). The findings suggest that multilingual testing is essential to understanding the developmental environment and cognitive growth of multilingual children.